URGENSI KEPESERTAAN JAMINAN KESEHATAN NASIONAL (JKN) DALAM PENDAFTARAN PERALIHAN HAK ATAS TANAH KARENA JUAL BELI - Nikita Dwi Maharani (2022)
The National Health Insurance (JKN) is a form of responsibility of the Indonesian state in terms of realizing the welfare of the Indonesian people. The implementation of the National Health Insurance program continues to be evaluated until it reaches the goal of providing optimal health insurance for the Indonesian people as a whole. The presence of Presidential Instruction Number 1 of 2022 concerning Optimization of National Health Insurance is one form of efforts to maximize the implementation of JKN. The Presidential Instruction in question involves, among others, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. In relation to its function, it is instructed to ensure that every application for registration of land rights due to sale and purchase includes evidence of active participants in the JKN program. This research is a critical study of the urgency of active participation in the National Health Insurance program as a condition for registration of land rights due to buying and selling, in order to realize legal harmony in implementing comprehensive and optimal JKN ideals for all Indonesian people. The study was conducted using a normative juridical method. Examine secondary data related to the focus of the problem. The results of this study indicate that for the implementation of registration of land rights due to buying and selling by including evidence of active participation in the National Health Insurance, a clear and firm form of regulation is needed. This is to obtain legal certainty, so that its implementation is clear, not misguided, and in line with statutory regulations.